Multi-WSN Simulator with Log Data for Efficient Sensing on Internet of Things - Young-Sik Jeong; Hyun-Woo Kim; Neil Y. Yen; Jong Hyuk Park (International Journal of Distributed Sensor Networks)
WSN (wireless sensor network) technology came to become fairly activated and as WSN is a part of the world's environment, research on it is considered important. WSN automated life and work; miniaturized wireless sensor nodes enable observational measurement in regions where access by humans is difficult or periodic sensing data is necessary. Thousands of such sensor nodes are needed. However, when they are wrongly placed in an observed area, sensor node batteries may run out fast or disconnection may result, which may trigger the loss of sensing data by sensor nodes and create an enormous cost. Moreover, even though sensor nodes have the same function, there are different kinds; therefore, it is difficult to select and place optimal sensor nodes. Accordingly, this paper proposed the WS3L (wireless sensor simulator using sensor log) as a simulator aimed at the composition of a more efficient sensing infrastructure and problem analysis for Internet of Things. This WS3L utilized sensor log data for precise prediction, not merely execution depending on simulators developed earlier. This WS3L read sensor log data of the observed area from the user and provided various analysis functions to examine problems.